2012
DOI: 10.4028/www.scientific.net/amm.152-154.112
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Stability of Poplar Wood after Densification Combined with Heat Treatment

Abstract: Hybrid poplar boards were subjected to thermo-mechanical densification combined with heat treatment. Hydroscopicity and hygroscopicity of the treated samples were measured. The results showed that dimensional stability of the samples was influenced by compression set significantly. The higher the compression set, the greater the swelling of the samples. On the contrary, the influence of densification temperature and duration was not significant. Thermal modification significantly reduced hydroscopicity and hyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It was determined that there was a strong positive linear relationship between compression and the swelling ratio. In similar studies, it was demonstrated that the compression parameters remarkably affect the dimensional stability of the samples and that greater swelling occurs in the samples densified with a higher compression level (Lamason and Gong 2007;Ünsal et al 2011;Cai et al 2012;Pelit et al 2014;Budakçı et al 2015;Pelit et al 2016). It was also stated by Cai et al (2012) that the compression time and temperature are not important in terms of dimensional stability.…”
Section: Radial and Tangential Swellingmentioning
confidence: 93%
“…It was determined that there was a strong positive linear relationship between compression and the swelling ratio. In similar studies, it was demonstrated that the compression parameters remarkably affect the dimensional stability of the samples and that greater swelling occurs in the samples densified with a higher compression level (Lamason and Gong 2007;Ünsal et al 2011;Cai et al 2012;Pelit et al 2014;Budakçı et al 2015;Pelit et al 2016). It was also stated by Cai et al (2012) that the compression time and temperature are not important in terms of dimensional stability.…”
Section: Radial and Tangential Swellingmentioning
confidence: 93%
“…Heat treatment can also be used to improve the dimensional stability of OSB boards, plywood [127], densified wood [121,128], and other wood composites [129].…”
Section: Heat Treatmentmentioning
confidence: 99%
“…The increase in density occurs as a result of the compaction (Unsal et al 2011, Arruda and Del Menezzi 2013, Cabral et al 2022. Compaction directly influences dimensional stability, with a tendency for swelling in samples with higher compression rates (Unsal et al 2011, Cai et al 2012.…”
Section: Resultsmentioning
confidence: 99%